Knowledge management in projects - Pereira, L. (2021)
Knowledge transfer in project-based organizations has been recognized as a productivity and economic growth promoter that is currently not properly managed. Therefore, it is critical to investigate the importance of knowledge regarding its acquisition, use, and transfer across all departments of an organization. The main objective of this work was to evaluate how modern organizations from different businesssectors manage and share their knowledge by following the knowledge management and transfer life cycles when developing their projects. Organizational surveys were performed to project managers working in project management within in multiple Portuguese industries (or with representation in Portugal) from multiple business sectors and holding different hierarchical positions. The presentstudy revealed that most companies can identify, capture, and retain the relevant knowledge, and apply it to the development of other projects. Thus, the importance of implementing the knowledge management transfer to other projectsis crucial forsuccessful project implementation and management